Cardioprotective effects of inorganic nitrate/nitrite in chronic anthracycline cardiotoxicity: Comparison with dexrazoxane - Lenčová-Popelová, Olga; Jirkovský, Eduard; Jansová, Hana; Jirkovská-Vávrová, Anna; Vostatková-Tichotová, Lucie; Mazurová, Yvona; Adamcová, Michaela; Chládek, Jaroslav; Hroch, Miloš; Pokorná, Zuzana; Geršl, Vladimír; Šimůnek, Tomáš; et al. (Journal of molecular and cellular cardiology, 2016)
Dexrazoxane (DEX) is a clinically available cardioprotectant that reduces the toxicity induced by anthracycline (ANT) anticancer drugs; however, DEX is seldom used and its action is poorly understood. Inorganic nitrate/nitrite has shown promising results in myocardial ischemia-reperfusion injury and recently in acute high-dose ANT cardiotoxicity. However, the utility of this approach for overcoming clinically more relevant chronic forms of cardiotoxicity remains elusive. Hence, in this study, the protective potential of inorganic nitrate and nitrite against chronic ANT cardiotoxicity was investigated, and the results were compared to those using DEX. Chronic cardiotoxicity was induced in rabbits with daunorubicin (DAU). Sodium nitrate (1g/L) was administered daily in drinking water, while sodium nitrite (0.15 or 5mg/kg) or DEX (60mg/kg) was administered parenterally before each DAU dose. Although oral nitrate induced a marked increase in plasma NOx, it showed no improvement in DAU-induced mortality, myocardial damage or heart failure. Instead, the higher nitrite dose reduced the incidence of end-stage cardiotoxicity, prevented related premature deaths and significantly ameliorated several molecular and cellular perturbations induced by DAU, particularly those concerning mitochondria. The latter result was also confirmed in vitro. Nevertheless, inorganic nitrite failed to prevent DAU-induced cardiac dysfunction and molecular remodeling in vivo and failed to overcome the cytotoxicity of DAU to cardiomyocytes in vitro. In contrast, DEX completely prevented all of the investigated molecular, cellular and functional perturbations that were induced by DAU. Our data suggest that the difference in cardioprotective efficacy between DEX and inorganic nitrite may be related to their different abilities to address a recently proposed upstream target for ANT in the heart - topoisomerase IIβ.
Keywords: rozvrh dávkování léků; DNA vazebné proteiny; Animals; Rabbits; Nitrates; kardiotonika; DNA-topoisomerasy typu II; intravenózní infuze; protinádorová antibiotika; Myocytes, Cardiac; kardiotoxicita; daunomycin; Drug Administration Schedule; Anthracyclines; Antibiotics, Antineoplastic; dexrazoxan; dusitan sodný; Cardioprotection; Dexrazoxane; Sodium Nitrite; Male; Infusions, Intravenous; DNA Topoisomerases, Type II; Daunorubicin; DNA-Binding Proteins; Cardiotonic Agents; králíci; Inorganic nitrate and nitrite; zvířata; mužské pohlaví; dusičnany; Myocardium; myokard; Cardiotoxicity; kardiomyocyty